Overcoming Immunosuppression: The Role of Tumor- Infiltrating Tregs and Their Key Target CCR8 in Immunotherapy Resistance and Therapeutic Strategies - Ma, Hanyu (Exploring Science Academic Conference Series, 2026)
The immunosuppressive tumor microenvironment (TME), orchestrated largely by tumor -infiltrating regulatory T cells (TI -Tregs), represents a critical barrier to effective cancer immunotherapy. This review focuses on the chemokine receptor CCR8, which has recently emerged as a highly promising and specific target for therapeutic intervention due to its preferential and stable expression on highly suppressive TI -Treg subsets. We synthesize current evidence demonstrating that CCR8 is selectively upregulated on TI -Tregs across multiple solid tumor types, where its expression correlates with poor patient prognosis and resistance to immune checkpoint inhibitors (ICIs). This expression pattern —enriched within the tumor but minimal in peripheral blood and normal tissues —provides a compelling rationale for tumor -selective targeting. We critically examine the primary therapeutic strategies under development, including ADCC -enhanced monoclonal antibodies, which have shown the most clinical promise, alongside bispecific antibodies and small molecule antagonists. While early -phase clinical trials report encouraging safety and on -target pharmacodynamic activity, the field faces significant challenges. These include unresolved questions regarding CCR8’s functional role versus its value as a targeting biomarker, a lack of validated predictive biomarkers for patient stratification, and the physical barriers to effective drug delivery in solid tumors. This review aims to provide a comprehensive and nuanced understanding of CCR8 biology and to outline the key steps necessary for the successful clinical translation of CCR8-targeted therapies.